Konsumsi Cokelat Bubuk Dapat Menurunkan Tekanan Darah Pada Lansia : Consuming Cocoa Powder Can Lower Blood Pressure in the Elderly - Jainero, Leovik; Yuliza, Emi; Lestari, Nur Eni (MPI Press, 2022)
Background: Hypertension is a factor that can lead to the development of diseases such as heart attacks, kidney failure, and strokes. The habit of consuming cocoa powder has a positive influence on blood pressure control. Objective: The purpose of this study is to determine the effect of cocoa powder consumption on blood pressure in the elderly. Method: The research design used is quasi-experimental and employed a one-group pre-post test design with 15 respondents. Data collection in this study was done using observation sheets. The research analysis used an independent T-test. Results: The results of this study showed that among the 15 respondents, it was observed that systolic and diastolic blood pressure was in the moderate to severe range before consuming cocoa powder, and after consuming cocoa powder, the blood pressure became mild to moderate. Conclusion: This research describes that there is an influence of cocoa powder consumption on blood pressure in the elderly (p=0.000).